Assessment of Decontamination and Reuse of Disposable Filter Funnels Used in Microbiological Water Quality Tests - Camille Zimmer; Alexandra Cassivi; Celia C Baía; Elizabeth Tilley; Robert Bain; Richard Johnston; Caetano C Dorea (SAGE Publishing, 2021)
To monitor safely managed drinking water services, an increasing number of countries have integrated water quality testing for Escherichia coli into nationally-representative household surveys such as the Multiple Indicator Cluster Surveys (MICS). However, plastic waste generated during such water quality testing programs, mostly through the use of pre-sterilized disposable materials, is non-negligible. The objective of this study was to evaluate several re-use protocols for disposable filter funnels used by the MICS water quality test kits. Decontamination and re-use protocols were assessed in centralized laboratory and decentralized field settings and neither yielded positive results. Re-use of 100 mL sterile funnels decontaminated with an alcohol wipe resulted in a higher incidence of false positive results (i.e., positive contamination when processing sterile water), both in the laboratory and field; therefore, a higher proportion of positives tests can be expected if these components are re-used. Further improvements to the decontamination technique and training are needed before material re-use can be reliably adopted. Autoclaving the funnels for re-use is feasible, provided that there is capacity to re-package and distribute funnels in a sterile manner.